Battery, energy storage device and energy storage system
By designing an appropriate adhesive layer structure in the battery separator and adjusting the expansion direction of the negative electrode sheet, the wrinkle problem caused by the expansion of the negative electrode sheet of the battery is solved, extending the cycle life of the battery and improving the dynamic performance.
Patent Information
- Application Number
- CN202510155689.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-05-09
AI Technical Summary
The negative electrode plate of the battery is pleated due to expansion and contraction during charging and discharging, which reduces the battery's capacity and cycle life.
By designing the first adhesive layer and the second adhesive layer in the separator of the battery, controlling the peel strength and coating amount, ensuring the relationship between 0.85≤(Fc·Wc)/(Fa·Wa)≤6.36, adjusting the expansion direction and strength of the negative electrode sheet, and reducing the relative displacement with the separator and the positive electrode sheet.
It effectively suppresses the lateral expansion of the negative electrode sheet, reduces the occurrence of wrinkles, extends the cycle life of the battery, and improves the kinetic performance.
Smart Images

Figure CN119965371A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and specifically to a battery, an energy storage device and an energy storage system. Background Art
[0002] With the growing demand for large-capacity energy storage batteries, the coating thickness design of battery electrodes is getting higher and higher, resulting in greater expansion and contraction of the thickness of the negative electrode plates during normal charging and discharging of the battery, which in turn causes wrinkles on the interface of the negative electrode plates, thereby reducing the capacity and cycle life of the battery. Summary of the invention
[0003] The embodiment of the present application provides a battery whose negative electrode plate is less prone to wrinkles and has a longer cycle life.
[0004] In a first aspect, an embodiment of the present application provides a battery, comprising: a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, the separator comprises a base film, a first adhesive layer and a second adhesive layer, the first adhesive layer is located between the base film and the positive electrode sheet, and is used to bond the base film to the positive electrode sheet, and the second adhesive layer is located between the base film and the negative electrode sheet, and is used to bond the base film to the negative electrode sheet;
[0005] The battery satisfies the relationship: 0.85≤(Fc·Wc) / (Fa·Wa)≤6.36;
[0006] Among them, Fc is the peeling strength between the first adhesive layer and the positive electrode sheet, Wc is the coating amount of the first adhesive layer per unit area on the base film, Fa is the peeling strength between the second adhesive layer and the negative electrode sheet, and Wa is the coating amount of the second adhesive layer per unit area on the base film.
[0007] In some embodiments, the battery satisfies the relationship: 2.16≤(Fc·Wc) / (Fa·Wa)≤6.20.
[0008] In some embodiments, the peel strength Fc between the first adhesive layer and the positive electrode sheet is in the range of: Fc ≥ 2.1 N / m.
[0009] In some embodiments, the peel strength Fa between the second adhesive layer and the negative electrode sheet is in the range of Fa≥0.5 N / m.
[0010] In some embodiments, the peel strength Fa between the second adhesive layer and the negative electrode sheet is in the range of 0.5 N / m≤Fa≤2.2 N / m.
[0011] In some embodiments, the coating amount Wc per unit area of the first adhesive layer on the base film is in the range of: 0.1 g / m 2 ≤Wc≤0.65g / m 2 The coating amount Wa of the second adhesive layer per unit area on the base film is in the range of: 0.1 g / m 2 ≤Wa≤0.65g / m 2 .
[0012] In some embodiments, the first adhesive layer and the second adhesive layer both include an adhesive, and the total mass proportion of the adhesive in the first adhesive layer and the second adhesive layer is P%, then the battery also satisfies the relationship: 0.05≤(Fc·Wa) / (Fa·Wc·P)≤1.39.
[0013] In some embodiments, the battery further satisfies the relationship: 0.05≤(Fc·Wa) / (Fa·Wc·P)≤0.86.
[0014] In some embodiments, the total mass percentage P% of the adhesive in the first adhesive layer and the second adhesive layer is in the range of: 2%≤P%≤25%.
[0015] In a second aspect, an embodiment of the present application further provides an energy storage device, comprising:
[0016] The housing; and
[0017] A plurality of batteries according to the embodiments of the present application are contained in the box.
[0018] In a third aspect, an embodiment of the present application further provides an energy storage system, comprising: an electric energy conversion device and the energy storage device described in the embodiment of the present application, the electric energy conversion device being electrically connected to the energy storage device, the electric energy conversion device being used to convert other forms of energy into electric energy, and the energy storage device being used to store the electric energy.
[0019] During the battery charge and discharge cycle, the negative electrode plate continuously undergoes lithium removal and lithium insertion. During the process of lithium insertion in the negative electrode plate, the negative electrode plate has an outward expansion force along its extension plane and an expansion force in the thickness direction. Since the positive electrode plate, the diaphragm and the negative electrode plate are bonded by the first bonding layer and the second bonding layer, the negative electrode plate will exert an outward expansion force on the diaphragm and the positive electrode plate along their extension plane, and the positive electrode plate and the diaphragm have a reaction force on the negative electrode plate along their extension plane to suppress the expansion inward. In this embodiment, by designing the relationship between the peel strength Fc between the first adhesive layer and the positive electrode sheet, the coating amount Wc of the first adhesive layer per unit area on the base film, the peel strength Fa between the second adhesive layer and the negative electrode sheet, and the coating amount Wa of the second adhesive layer per unit area on the base film, 0.85≤(Fc·Wc) / (Fa·Wa)≤6.36, so that during the process of lithium insertion, the negative electrode sheet expands more along its thickness direction (i.e., the stacking direction of the positive electrode sheet, the separator and the negative electrode sheet), and the expansion of the negative electrode sheet along its extension plane is suppressed, thereby reducing the relative displacement between the negative electrode sheet and the separator and the positive electrode sheet during the lithium insertion process, which can make the negative electrode sheet less likely to wrinkle, thereby making the battery have a longer cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 It is a schematic diagram of the structure of a battery according to an embodiment of the present application.
[0022] Figure 2 The battery of one embodiment of the present application is Figure 1 Schematic diagram of the cross-sectional structure in the AA direction.
[0023] Figure 3 It is a schematic cross-sectional structural diagram of an electrode assembly according to an embodiment of the present application.
[0024] Figure 4 It is a schematic diagram of the forces acting on the positive electrode sheet, the separator and the negative electrode sheet according to an embodiment of the present application.
[0025] Figure 5 It is a schematic diagram of the cross-sectional structure of a positive electrode plate according to an embodiment of the present application.
[0026] Figure 6 It is a schematic diagram of the cross-sectional structure of a negative electrode plate according to an embodiment of the present application.
[0027] Figure 7 It is a structural block diagram of an energy storage system according to an embodiment of the present application.
[0028] Figure 8 This is an application scenario diagram of an energy storage system according to an embodiment of the present application.
[0029] Fig. 9 It is a schematic structural diagram of an energy storage device according to an embodiment of the present application.
[0030] Description of reference numerals:
[0031] 100-battery, 101-electrode assembly, 110-positive electrode plate, 111-positive current collector, 112-positive active layer, 120-diaphragm, 121-base film, 122-first bonding layer, 123-second bonding layer, 130-negative electrode plate, 131-negative current collector, 132-negative active layer, 140-shell, 141-receiving cavity, 150-end cover assembly, 200-energy storage device, 210-casing, 300-energy storage system, 310-electric energy conversion device. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0034] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0035] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0036] At present, the generation of green electricity generally relies on photovoltaics, wind power, and hydropower, etc. However, wind and solar energy generally have problems of strong intermittency and large volatility, which will cause instability in the power grid, insufficient electricity during peak hours, and too much electricity during valley hours. Unstable voltage will also cause damage to electricity. Therefore, insufficient electricity demand or insufficient grid acceptance capacity may cause the problem of "abandoning wind and solar power". To solve these problems, we must rely on energy storage. That is, converting electrical energy into other forms of energy through physical or chemical means and storing it, and converting energy into electrical energy and releasing it when needed. In simple terms, energy storage is like a large "power bank". When photovoltaic and wind energy are sufficient, electrical energy is stored and the stored electricity is released when needed.
[0037] Batteries are the smallest energy storage units of energy storage devices and energy storage systems. The performance of batteries directly affects the performance and application of energy storage devices and energy storage systems.
[0038] With the growing demand for large-capacity energy storage batteries, the coating thickness design of battery electrodes is getting higher and higher, resulting in greater expansion and contraction of the thickness of the negative electrode plates during normal charging and discharging of the battery, which in turn causes wrinkles on the interface of the negative electrode plates, thereby reducing the capacity and cycle life of the battery.
[0039] See also Figures 1 to 3 , the embodiment of the present application provides a battery 100, the battery 100 includes a positive electrode sheet 110, a separator 120 and a negative electrode sheet 130, the separator 120 is located between the positive electrode sheet 110 and the negative electrode sheet 130, the separator 120 includes a base film 121, a first adhesive layer 122 and a second adhesive layer 123, the first adhesive layer 122 is located between the base film 121 and the positive electrode sheet 110, and is used to bond the base film 121 to the positive electrode sheet 110, and the second adhesive layer 123 is located between the base film 121 and the negative electrode sheet 130, and is used to bond the base film 121 to the negative electrode sheet 130;
[0040] The battery 100 satisfies the relationship: 0.85≤(Fc·Wc) / (Fa·Wa)≤6.36;
[0041] Among them, Fc is the peeling strength between the first adhesive layer 122 and the positive electrode plate 110, Wc is the coating amount per unit area of the first adhesive layer 122 on the base film 121, Fa is the peeling strength between the second adhesive layer 123 and the negative electrode plate 130, and Wa is the coating amount per unit area of the second adhesive layer 123 on the base film 121.
[0042] The battery 100 of the embodiment of the present application can be applied to energy storage devices such as a battery 100 module (also called an energy storage module), a small energy storage box, and a large energy storage cabinet. The energy storage device is used to store electrical energy and can supply electrical loads such as street lamps and household appliances for use when the electricity price is at a peak, or to supply power when the power grid is out of power / power outage.
[0043] Optionally, the battery 100 may be, but is not limited to, at least one of a lithium ion battery 100 , a sodium ion battery 100 , a magnesium ion battery 100 , and the like.
[0044] It can be understood that the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked in sequence to form the electrode assembly 101. The electrode assembly 101 can be, but is not limited to, a winding structure, a laminated structure, etc., which is not specifically limited in the present application.
[0045] The first adhesive layer 122, the base film 121 and the second adhesive layer 123 may be stacked in sequence. Before the electrode assembly 101 is wound, the positive electrode sheet 110, the first adhesive layer 122, the base film 121, the second adhesive layer 123 and the negative electrode sheet 130 may be stacked in sequence.
[0046] Specifically, the value of (Fc·Wc) / (Fa·Wa) can be but is not limited to 0.85, 0.9, 0.95, 1.0, 1.3, 1.5, 1.8, 2.0, 2.16, 2.3, 2.5, 2.8, 3.0, 3.3, 3.5, 3.8, 4.0, 4.3, 4.5, 4.8, 5.0, 5.3, 5.5, 5.8, 6.0, 6.2, 6.36, etc. If (Fc·Wc) / (Fa·Wa) is too small, the bonding force between the diaphragm 120 and the positive electrode sheet 110 is relatively weak, and the bonding force between the diaphragm 120 and the negative electrode sheet 130 is relatively strong. During the process of shrinkage and expansion of the negative electrode sheet 130 during lithium extraction and insertion, the expansion force of the negative electrode sheet 130 pulls the diaphragm 120 to move, so that the negative electrode sheet 130 is prone to uneven force at corners or local areas, so that the negative electrode sheet 130 is prone to wrinkling or swelling, reducing the capacity and cycle capacity retention rate of the battery 100; if (Fc·Wc) / (Fa·Wa) is too large, the bonding force between the positive electrode sheet 110 and the diaphragm 120 is too strong, and the first bonding layer 122 is prone to block the pores of the positive active layer on the surface of the positive electrode sheet 110, reducing the ion mobility of the positive active layer and reducing the dynamic performance of the battery 100. When 0.85≤(Fc·Wc) / (Fa·Wa)≤6.36, the negative electrode plate 130 is less likely to wrinkle, and the positive electrode active layer has a higher ion mobility, so that the battery 100 has a longer cycle life and higher kinetic performance.
[0047] like Figure 4As shown, during the charge and discharge cycle of the battery 100, the negative electrode plate 130 continuously undergoes lithium removal and lithium insertion. During the lithium insertion process of the negative electrode plate 130, the negative electrode plate 130 has an outward expansion force along its extension plane and an expansion force in the thickness direction. Since the positive electrode plate 110, the diaphragm 120 and the negative electrode plate 130 are bonded by the first bonding layer 122 and the second bonding layer 123, the negative electrode plate 130 will exert an outward expansion force along the extension plane on the diaphragm 120 and the positive electrode plate 110, and the positive electrode plate 110 and the diaphragm 120 have a reaction force on the negative electrode plate 130 to suppress the expansion inward along the extension plane. In this embodiment, by designing the relationship between the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110, the coating amount Wc of the first adhesive layer 122 per unit area on the base film 121, the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130, and the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121, 0.85≤(Fc·Wc) / (Fa·Wa)≤6.36 , so that during the lithium insertion process, the negative electrode sheet 130 expands more along its thickness direction (i.e., the stacking direction of the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130), suppressing the expansion of the negative electrode sheet 130 along its extension plane, thereby reducing the relative displacement between the negative electrode sheet 130 and the separator 120 and the positive electrode sheet 110 during the lithium insertion process, making the negative electrode sheet 130 less likely to wrinkle, thereby allowing the battery 100 to have a longer cycle life.
[0048] In some embodiments, the battery 100 satisfies the relationship: 2.16≤(Fc·Wc) / (Fa·Wa)≤6.20. Specifically, the value of (Fc·Wc) / (Fa·Wa) may be, but is not limited to, 2.16, 2.3, 2.5, 2.8, 3.0, 3.3, 3.5, 3.8, 4.0, 4.3, 4.5, 4.8, 5.0, 5.3, 5.5, 5.8, 6.0, 6.2, etc. In this way, the negative electrode sheet 130 is less likely to wrinkle, and the positive active layer of the positive electrode sheet 110 has a higher ion mobility, so that the battery 100 has a longer cycle life and higher kinetic performance.
[0049] In some embodiments, the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110 is in the range of: Fc ≥ 2.1 N / m.
[0050] Specifically, the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110 can be, but is not limited to, 2.1 N / m, 2.3 N / m, 2.5 N / m, 2.8 N / m, 3.0 N / m, 3.3 N / m, 3.5 N / m, 3.8 N / m, 4.0 N / m, 4.3 N / m, 4.5 N / m, 4.8 N / m, 5.0 N / m, 5.3 N / m, 5.5 N / m, 5.8 N / m, 6.0 N / m, 6.3 N / m, 6.5 N / m, 6.8 N / m, 7.0 N / m, 7.5 N / m, 8.0 N / m, 8.5 N / m, 9.0 N / m, 9.5 N / m, 10.0 N / m, 10.5 N / m, 11.0 N / m, etc.
[0051] In this embodiment, if the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110 is too small, the positive electrode sheet 110 and the separator 120 will reduce the restraint and inhibition of the lateral expansion of the negative electrode sheet 130 during the lithium insertion process of the negative electrode sheet 130, so that the negative electrode sheet 130 is prone to disorderly expansion during the lithium insertion process, and the negative electrode sheet 130 is prone to wrinkles during repeated charge and discharge, which reduces the cycle life of the battery 100. When the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110 is in the range of: Fc ≥ 2.1N / m, the probability of expansion of the negative electrode sheet 130 during repeated charge and discharge can be better reduced, thereby improving the cycle life of the battery 100.
[0052] In some embodiments, the peel strength Fa between the second adhesive layer 123 and the negative electrode plate 130 is in the range of Fa≥0.5 N / m.
[0053] Specifically, the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 can be, but is not limited to, 0.5 N / m, 0.53 N / m, 0.55 N / m, 0.58 N / m, 0.6 N / m, 0.63 N / m, 0.65 N / m, 0.68 N / m, 0.7 N / m, 1.0 N / m, 1.3 N / m, 1.5 N / m, 1.8 N / m, 2.0 N / m, 2.2 N / m, 2.3 N / m, 2.5 N / m, 2.8 N / m, 3.0 N / m, 3.2 N / m, 3.5 N / m, etc.
[0054] In the present embodiment, if the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 is too small, during the expansion of the negative electrode sheet 130 due to lithium insertion, the separator 120 cannot suppress the expansion of the negative electrode sheet 130 along its extension plane (i.e., the plane perpendicular to the stacking direction of the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130), so that the negative electrode sheet 130 expands disorderly in its extension plane and thickness direction, and the expansion of the negative electrode sheet 130 along its extension plane easily causes the negative electrode sheet 130 to wrinkle; when the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 is ≥0.5N / m, this can better avoid the expansion of the negative electrode sheet 130 along its extension plane during the lithium insertion process, thereby better reducing the probability of wrinkling of the negative electrode sheet 130 and improving the cycle life of the battery 100.
[0055] In some embodiments, the range of the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 is: 0.5N / m≤Fa≤2.2N / m. When the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 is large, although the probability of wrinkling of the negative electrode sheet 130 can be improved, when the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 is too large, the negative active layer of the negative electrode sheet 130 is prone to material shedding during the lithium insertion process of the negative electrode sheet 130. During the long cycle process of repeated charge and discharge of the battery 100, as the second adhesive layer 123 gradually ages, the risk of material shedding of the negative active layer of the negative electrode sheet 130 increases, thereby reducing the cycle life of the battery 100. When the peel strength between the second adhesive layer 123 and the negative electrode plate 130 is in the range of 0.5N / m≤Fa≤0.65N / m, not only can the negative electrode plate 130 be less likely to wrinkle and fall off during repeated charge and discharge of the battery 100, but the cycle life of the battery 100 can also be better improved.
[0056] In some embodiments, the coating amount Wc per unit area of the first adhesive layer 122 on the base film 121 is in the range of: 0.1 g / m 2 ≤Wc≤0.65g / m 2 .
[0057] Specifically, the coating weight Wc per unit area of the first adhesive layer 122 on the base film 121 may be, but is not limited to, 0.1 g / m 2 , 0.13g / m 2 , 0.15g / m 2 , 0.18g / m 2 , 0.2g / m 2 , 0.23g / m 2 , 0.25g / m2 , 0.28g / m 2 , 0.3g / m 2 , 0.33g / m 2 , 0.35g / m 2 , 0.38g / m 2 , 0.4g / m 2 , 0.43g / m 2 , 0.45g / m 2 , 0.48g / m 2 , 0.5g / m 2 , 0.53g / m 2 , 0.55g / m 2 , 0.58g / m 2 , 0.6g / m 2 , 0.63g / m 2 , 0.65g / m 2 wait.
[0058] In this embodiment, the coating amount Wc of the first adhesive layer 122 per unit area on the base film 121 is too small, and the constraint of the positive electrode sheet 110 on the diaphragm 120 is too small. In the process of lithium extraction of the negative electrode sheet 130, the diaphragm 120 is easily moved by the negative electrode sheet 130, so that the diaphragm 120 and the negative electrode sheet 130 are prone to wrinkles; if the coating amount Wc of the first adhesive layer 122 per unit area on the base film 121 is too large, the first adhesive layer 122 is prone to fall off, thereby reducing the cycle performance of the battery 100.
[0059] Optionally, the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121 is in the range of: 0.1 g / m 2 ≤Wa≤0.65g / m 2 .
[0060] Specifically, the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121 may be, but is not limited to, 0.1 g / m 2 , 0.13g / m 2 , 0.15g / m 2 , 0.18g / m 2 , 0.2g / m 2 , 0.23g / m 2 , 0.25g / m 2 , 0.28g / m 2 , 0.3g / m 2 , 0.33g / m 2 , 0.35g / m 2 , 0.38g / m 2 , 0.4g / m 2, 0.43g / m 2 , 0.45g / m 2 , 0.48g / m 2 , 0.5g / m 2 , 0.53g / m 2 , 0.55g / m 2 , 0.58g / m 2 , 0.6g / m 2 , 0.63g / m 2 , 0.65g / m 2 wait.
[0061] In the present embodiment, the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121 is too small, and the restraint of the separator 120 on the negative electrode plate 130 is too small. During the process of lithium insertion and extraction of the negative electrode plate 130, the inhibitory effect of the separator 120 on the expansion of the negative electrode plate 130 along its extension plane (i.e., the lateral direction) is reduced, so that the probability of disordered expansion of the negative electrode plate 130 during the lithium insertion process is increased, and the negative electrode plate 130 is prone to wrinkling; if the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121 is too large, the negative active layer of the negative electrode plate 130 is prone to material shedding during the lithium insertion process of the negative electrode plate 130. During the long cycle process of repeated charge and discharge of the battery 100, as the second adhesive layer 123 gradually ages, the risk of material shedding of the negative active layer of the negative electrode plate 130 increases, thereby reducing the cycle life of the battery 100.
[0062] In some embodiments, the first adhesive layer 122 and the second adhesive layer 123 both include an adhesive, and the total mass proportion of the adhesive in the first adhesive layer 122 and the second adhesive layer 123 is P%, then the battery 100 also satisfies the relationship: 0.05≤(Fc·Wa) / (Fa·Wc·P)≤1.39.
[0063] Optionally, the mass fraction of the adhesive in the first adhesive layer 122 is equal to the mass fraction of the adhesive in the second adhesive layer 123 .
[0064] Specifically, the value of (Fc·Wa) / (Fa·Wc·P) can be, but is not limited to, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.39, etc.
[0065] In this embodiment, if (Fc·Wa) / (Fa·Wc·P) is too small, the separator 120 and the negative electrode plate 130 are too firmly bonded, so that the negative active layer of the negative electrode plate 130 is prone to material loss during the process of lithium insertion and extraction of the negative electrode plate 130; if (Fc·Wa) / (Fa·Wc·P) is too large, the separator 120 and the positive electrode plate 110 are too firmly bonded, and the first bonding layer 122 is prone to adhere to the surface of the positive electrode plate 110. When 0.05≤(Fc·Wa) / (Fa·Wc·P)≤1.39, the negative electrode plate 130 is not prone to wrinkles and material loss during repeated charge and discharge, thereby improving the cycle life of the battery 100.
[0066] In some embodiments, the battery 100 also satisfies the relationship: 0.05≤(Fc·Wa) / (Fa·Wc·P)≤0.86. Specifically, the value of (Fc·Wa) / (Fa·Wc·P) may be, but is not limited to, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.86, etc. In this way, the negative electrode sheet 130 is not prone to wrinkles and material drop during repeated charge and discharge, thereby improving the cycle life of the battery 100.
[0067] In some embodiments, the total mass percentage P% of the adhesive in the first adhesive layer 122 and the second adhesive layer 123 is in the range of 2%≤P%≤25%.
[0068] Specifically, the total mass proportion P% of the adhesive in the first adhesive layer 122 and the second adhesive layer 123 can be but is not limited to 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, etc.
[0069] In this embodiment, if the total mass proportion P% of the adhesive in the first adhesive layer 122 and the second adhesive layer 123 is too low, the first adhesive layer 122 is not firmly bonded to the base film 121 and the positive electrode sheet 110, and the separator 120 is prone to wrinkles, thereby causing the negative electrode sheet 130 to wrinkle. Similarly, the second adhesive layer 123 is not firmly bonded to the base film 121 and the negative electrode sheet 130, and the second adhesive layer 123 is prone to wrinkles. If the total mass proportion P% of the adhesive described in 23 is too high, the cost of the first adhesive layer 122 and the second adhesive layer 123 will be increased, and the bonding force of the first adhesive layer 122 and the second adhesive layer 123 will be too strong. When the diaphragm 120 is too firmly bonded to the negative electrode plate 130, the negative active layer of the negative electrode plate 130 is prone to fall off during the process of lithium insertion and extraction of the negative electrode plate 130. When the diaphragm 120 is too firmly bonded to the positive electrode plate 110, the first adhesive layer 122 is prone to stick to the surface of the positive electrode plate 110.
[0070] Optionally, the mass fraction of the adhesive in the first adhesive layer 122 ranges from 2% to 25%. Specifically, the mass fraction of the adhesive in the first adhesive layer 122 may be, but is not limited to, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, etc. If the mass fraction of the adhesive in the first adhesive layer 122 is too low, the first adhesive layer 122 is not firmly bonded to the base film 121 and the positive electrode sheet 110, and the separator 120 is prone to wrinkles, thereby causing the negative electrode sheet 130 to wrinkle; if the mass fraction of the adhesive in the first adhesive layer 122 is too high, the cost of the first adhesive layer 122 is increased, and the bonding force of the first adhesive layer 122 is too strong, the separator 120 is too firmly bonded to the positive electrode sheet 110, and the first adhesive layer 122 is easily adhered to the surface of the positive electrode sheet 110.
[0071] Optionally, the mass fraction of the binder in the second adhesive layer 123 ranges from 2% to 25%. Specifically, the mass fraction of the binder in the second adhesive layer 123 may be, but is not limited to, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, etc. If the mass fraction of the binder in the second adhesive layer 123 is too low, the second adhesive layer 123 is not firmly bonded to the base film 121 and the negative electrode sheet 130, and the second adhesive layer 123 is prone to wrinkles; if the mass fraction of the binder in the second adhesive layer 123 is too high, the cost of the second adhesive layer 123 is increased, and the bonding force of the second adhesive layer 123 is too strong, the separator 120 is too firmly bonded to the negative electrode sheet 130, and the negative active layer of the negative electrode sheet 130 is prone to fall off during the process of lithium insertion and extraction of the negative electrode sheet 130.
[0072] Optionally, the adhesive includes polar groups, so that the first adhesive layer 122 and the second adhesive layer 123 have more suitable adhesive force, thereby better preventing the negative electrode plate 130 from wrinkling during the charge and discharge process and preventing the first adhesive layer 122 and the second adhesive layer 123 from falling off.
[0073] Alternatively, the polar group may be, but is not limited to, at least one of a hydroxyl group (—OH), a carboxyl group (—COOH), a maleic anhydride group (—COOOC—), a sulfonate group (—SO 3 H) and a pyrrolidone group (—NCO—).
[0074] Optionally, the adhesive may include, but is not limited to, at least one of polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide and polyethylene oxide, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, carboxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, polymaleic anhydride or polyvinyl pyrrolidone, etc. By using these adhesives, the first adhesive layer 122 and the second adhesive layer 123 can have more suitable adhesion, so as to better prevent the negative electrode plate 130 from wrinkling during the charge and discharge process and prevent the first adhesive layer 122 and the second adhesive layer 123 from falling off.
[0075] Optionally, the first adhesive layer 122 and the second adhesive layer 123 further include an adhesive main material.
[0076] Optionally, the main bonding material can be but is not limited to polyvinylidene fluoride (PVDF), functional poly (Norbornene-Conorbornene Dicarboxylic Acid-Co-HeptafluorobutylNorbornenimide), PNCI-based adhesive, styrene butadiene rubber (SBR), fluorinated polyimide (FPI), polyimide-siloxane (PIS), polyacrylonitrile (PAN), etc.
[0077] It should be noted that before the first bonding layer 122 and the second bonding layer 123 are formed, the bonding main material exists in a granular form, and the adhesive is dissolved in a solvent to disperse the bonding main material and make the bonding main material evenly distributed on the surface of the base film 121. The bonding main material mainly plays the role of bonding the base film 121 to the positive electrode plate 110 and the base film 121 to the negative electrode plate 130.
[0078] Optionally, the mass fraction of the main adhesive material in the first adhesive layer 122 ranges from 70% to 95%. Specifically, the mass fraction of the main adhesive material in the first adhesive layer 122 may be, but is not limited to, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, etc. If the mass fraction of the main adhesive material in the first adhesive layer 122 is too low, it is not conducive to the effective bonding between the base film 121 and the positive electrode sheet 110; if the mass fraction of the main adhesive material in the first adhesive layer 122 is too high, it is not conducive to the dispersion of the main adhesive material, so that the main adhesive material is unevenly distributed in the first adhesive layer 122, which also affects the bonding between the base film 121 and the positive electrode sheet 110.
[0079] Optionally, the mass fraction of the main adhesive material in the second adhesive layer 123 ranges from 70% to 95%. Specifically, the mass fraction of the main adhesive material in the second adhesive layer 123 may be, but is not limited to, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, etc. If the mass fraction of the main adhesive material in the second adhesive layer 123 is too low, it is not conducive to the effective bonding between the base film 121 and the negative electrode sheet 130; if the mass fraction of the main adhesive material in the second adhesive layer 123 is too high, it is not conducive to the dispersion of the main adhesive material, so that the main adhesive material is unevenly distributed in the second adhesive layer 123, which also affects the bonding between the base film 121 and the negative electrode sheet 130.
[0080] Optionally, the base film 121 may be but is not limited to at least one of a polypropylene microporous film (PP film for short), a polyethylene microporous film (PE film for short), a ceramic base film 121, a polyethylene-polypropylene (PP / PE) composite microporous film, a polyolefin microporous film, and the like.
[0081] Optionally, the diaphragm 120 further includes an alumina ceramic coating (referred to as CCS coating), and the alumina ceramic coating may be disposed between the base film 121 and the first adhesive layer 122 and / or between the base film 121 and the second adhesive layer 123 .
[0082] Optionally, the CCS coating includes an inorganic oxide (such as a high temperature resistant inorganic oxide) and sodium carboxymethyl cellulose.
[0083] Optionally, the porosity of the base film 121 ranges from 20% to 65%, for example, it may be but is not limited to 20%, 30%, 420%, 50%, 60%, 65%, etc.
[0084] Optionally, the thickness of the base film 121 is 7μm to 20μm. Specifically, the thickness of the base film 121 may be but is not limited to 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 16.5μm, 17μm, 17.5μm, 18μm, 20μm, etc.
[0085] Optionally, the width of the base film 121 ranges from 200 mm to 800 mm. Specifically, the width of the base film 121 may be, but is not limited to, 200 mm, 300 mm, 400 mm, 500 mm, 600 mm, 700 mm, 800 mm, etc. The width of the base film 121 may be designed according to the size of the battery 100.
[0086] See also Figure 5 Optionally, the positive electrode sheet 110 includes a positive current collector 111 and a positive active layer 112, and the positive active layer 112 is disposed on the surface of the positive current collector 111. It can be understood that the positive active layer 112 can cover one surface or two opposite surfaces of the positive current collector 111.
[0087] Optionally, the positive electrode current collector 111 may be, but is not limited to, an aluminum sheet.
[0088] Optionally, the positive electrode active layer 112 includes a positive electrode active material, a positive electrode conductor, a positive electrode binder and a positive electrode thickener.
[0089] Optionally, the positive electrode active material may be, but is not limited to, at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium iron phosphate, lithium titanate and lithium-rich manganese-based materials.
[0090] Optionally, the positive electrode conductive agent may be, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0091] Optionally, the positive electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene butadiene rubber (SBR).
[0092] Optionally, in the positive electrode active layer 112, the mass fraction of the positive electrode binder ranges from 2wt% to 4wt%. Specifically, in the positive electrode active layer 112, the mass fraction of the positive electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the positive electrode binder is too small, the positive electrode active layer 112 is prone to pulverization or slag; if the mass fraction of the positive electrode binder is too large, the energy density of the positive electrode sheet 110 is reduced.
[0093] Optionally, the positive electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).
[0094] See also Figure 6 Optionally, the negative electrode sheet 130 includes a negative electrode current collector 131 and a negative electrode active layer 132, and the negative electrode active layer 132 is disposed on the surface of the negative electrode current collector 131. It can be understood that the negative electrode active layer 132 can cover one surface or two opposite surfaces of the negative electrode current collector 131.
[0095] Optionally, the negative electrode current collector 131 may be, but is not limited to, a copper sheet.
[0096] Optionally, the negative electrode active layer 132 includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a negative electrode thickener.
[0097] Optionally, the negative electrode active material may be, but is not limited to, graphite.
[0098] Optionally, the negative electrode conductive agent may be, but is not limited to, at least one of conductive carbon black (SP for short), acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0099] Optionally, the negative electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, styrene-butadiene rubber, and the like.
[0100] Optionally, in the negative electrode active layer 132, the mass fraction of the negative electrode binder ranges from 2wt% to 4wt%. Specifically, in the negative electrode active layer 132, the mass fraction of the negative electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the negative electrode binder is too small, the negative electrode active layer 132 is prone to pulverization or slag; if the mass fraction of the negative electrode binder is too large, the energy density of the negative electrode plate 130 is reduced.
[0101] Optionally, the negative electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).
[0102] Please see again Figure 1 and Figure 2 Optionally, the battery 100 further includes a shell 140 and an end cover assembly 150 , wherein the shell 140 and the end cover assembly 150 enclose a receiving cavity 141 , and the receiving cavity 141 is used to receive the positive electrode plate 110 , the diaphragm 120 and the negative electrode plate 130 .
[0103] In some embodiments, the battery 100 further includes an electrolyte, which is disposed in the receiving cavity 141 and at least partially wets the positive electrode sheet 110 and the negative electrode sheet 130 .
[0104] Optionally, the electrolyte includes an electrolyte salt, an organic solvent and a film-forming additive.
[0105] Alternatively, the electrolyte salt may include, but is not limited to, lithium salt, sodium salt, and the like.
[0106] Optionally, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiODFP), lithium difluorobis(oxalatoborate) (LiODFB), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonate (CF3SO3Li), etc.
[0107] Optionally, the sodium salt may include, but is not limited to, at least one of sodium hexafluorophosphate (LiPF6), sodium tetrafluoroborate (LiBF4), sodium bis(fluorosulfonyl)imide (LiFSI), sodium bis(trifluoromethanesulfonyl)imide (LiTFSI), sodium bis(oxalatoborate) (LiBOB), sodium difluorobis(oxalatophosphate) (LiODFP), sodium difluorobis(oxalatoborate) (LiODFB), sodium difluorophosphate (LiPO2F2), sodium trifluoromethanesulfonate (CF3SO3Li), and the like.
[0108] Optionally, in the electrolyte, the molar concentration M of the electrolyte salt is in the range of 0.7mol / L≤M≤1.4mol / L. In the electrolyte, the molar concentration M of the electrolyte salt may be, but is not limited to, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, etc. If the molar concentration M of the electrolyte salt is too small, the concentration of free ions in the electrolyte is too small, which reduces the conductivity of the electrolyte and thus reduces the kinetic performance of the battery 100; if the molar concentration M of the electrolyte salt is too large, a portion of the electrolyte salt is likely to remain undissociated, and the viscosity of the electrolyte will increase, which in turn reduces the conductivity of the electrolyte and also reduces the kinetic performance of the battery 100. When the molar concentration M of the electrolyte salt in the electrolyte is in the range of 0.7 mol / L≤M≤1.4 mol / L, the electrolyte can have a higher conductivity, so that the battery 100 has better kinetic performance.
[0109] Optionally, the organic solvent includes at least one of a cyclic carbonate and a chain carbonate. Cyclic carbonate has a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode plate 130, but its viscosity is relatively large. Chain carbonate has a lower viscosity than cyclic carbonate, better electrochemical stability, and can improve the low-temperature performance of the electrolyte. Therefore, when a mixed solvent of cyclic carbonate and chain carbonate is used, the electrolyte can have a more suitable viscosity and low-temperature stability, and the battery 100 using the electrolyte can be better film-formed.
[0110] Optionally, the cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC for short), propylene carbonate (PC for short), etc. The dielectric constant of ethylene carbonate is much greater than that of propylene carbonate, and ethylene carbonate can better promote the formation of SEI film.
[0111] Optionally, the linear carbonate may include but is not limited to at least one of dimethyl carbonate (DMC for short), diethyl carbonate (DEC for short), ethyl methyl carbonate (EMC for short), and the like.
[0112] Optionally, in the electrolyte, the mass fraction of the organic solvent is 60wt% to 85wt%, specifically, but not limited to, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc.
[0113] Optionally, the organic solvent further comprises at least one of ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, γ-butyrolactone, and 2,2-difluoroethyl acetate.
[0114] Optionally, the film-forming additive includes at least one of fluoroethylene carbonate (FEC), diethylene sulfate (DTD), vinylene carbonate (VC), vinyl carbonate (VEC), tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, adiponitrile, succinonitrile, and 1,3,6-hexanetrinitrile.
[0115] Optionally, the mass fraction of the film-forming additive ranges from 0.3% to 3%. Specifically, the mass fraction of the film-forming additive may be, but is not limited to, 0.3%, 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc.
[0116] The battery 100 of the present application is further described below through specific embodiments.
[0117] Example 1 to Example 15, Comparative Example 1 to Comparative Example 7
[0118] The battery 100 of each embodiment and comparative example is prepared by the following steps:
[0119] (1) Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate is dissolved in a mixed solvent of fluoroethylene carbonate (FEC), ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a mass ratio of 1:1:1:1 to form an electrolyte, wherein the molar concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L.
[0120] (2) Preparation of positive electrode sheet 110: dissolving lithium iron phosphate (positive electrode active material), acetylene black (positive electrode conductive agent), polyvinylidene fluoride (positive electrode binder), and surfactant in N-methylpyrrolidone (NMP) solution in a weight ratio of 94:2:3:1 to prepare positive electrode slurry; using aluminum foil as positive electrode current collector 111, coating the positive electrode slurry on the positive electrode current collector 111, and drying to obtain positive electrode sheet 110; the coating weight on one side of the positive electrode sheet 110 is 320g / 1540.25mm2 , double-sided coating weight is 640g, 1540.25mm 2 between.
[0121] (3) Preparation of negative electrode sheet 130: Graphite is used as the negative electrode active material. Graphite, acetylene black (negative electrode conductive agent), styrene butadiene rubber (SBR, negative electrode binder), sodium carboxymethyl cellulose (CMC, negative electrode thickener), and polyvinyl alcohol-based aqueous adhesive are dissolved in deionized water in a ratio of 95.0:1.5:1.4:2.1, and stirred to obtain negative electrode slurry; copper foil is used as the negative electrode collector 131, and the negative electrode slurry is coated on the negative electrode collector 131. After drying, cold pressing, and die cutting, a graphite negative electrode sheet 130 is obtained; the single-sided coating weight of the negative electrode sheet 130 is 160 / 1540.25mm 2 , double-sided coating weight 320g, 1540.25mm 2 .
[0122] (4) Preparation of the diaphragm 120: A polyethylene film is used as the base film 121, and a first adhesive layer 122 and a second adhesive layer 123 are respectively formed on two opposite surfaces of the base film 121. The mass fraction of the adhesive in the first adhesive layer 122 and the second adhesive layer 123 are equal. The coating amount of the first adhesive layer 122 and the second adhesive layer 123 and the content of the adhesive in the first adhesive layer 122 and the second adhesive layer 123 are shown in Table 1 below.
[0123] (5) Assembly of battery 100: stack the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 in order, with the separator 120 located between the positive electrode sheet 110 and the negative electrode sheet 130 to play an isolating role, and then wind them into a core and perform hot pressing; place the hot pressed core into an aluminum shell, and remove moisture at 100°C to obtain a dry electrode assembly 101; after hot pressing, perform processes such as liquid injection, vacuum packaging, standing, formation, and shaping to complete the production of battery 100.
[0124] The following performance tests were performed on the battery 100 of each embodiment and comparative example:
[0125] (1) Peel strength test: After fully charging the battery 100, fully discharge it (i.e., discharge all the power), disassemble the battery 100, remove the electrode assembly 101, and use a HY-0580 universal tensile testing machine to test the peel strength between the first adhesive layer 122 and the positive electrode sheet 110, and between the second adhesive layer 123 and the negative electrode sheet 130.
[0126] (2) Wrinkle and material drop test: The battery 100 is subjected to a charge and discharge cycle test on a charge and discharge instrument (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010). The test temperature is 25°C, the cycle rate is 1C (i.e., both the charge rate and the discharge rate are 1C), and the charging voltage is 2.5V to 3.65V. After 10 charge and discharge cycles, the battery 100 is disassembled to observe the wrinkles of the negative electrode sheet 130 and the drop of the negative electrode sheet 130 or the first adhesive layer 122.
[0127] The test results of each embodiment and comparative example are shown in Table 1 below.
[0128] Table 1 Performance parameters of the battery 100 of each embodiment and comparative example
[0129]
[0130] (3) 500-cycle cycle performance test at 25°C: The battery 100 was subjected to a charge and discharge cycle test on a charge and discharge instrument (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010). The test temperature was 25°C, the cycle rate was 1C (i.e., both the charge rate and the discharge rate were 1C), the charging voltage was 2.5V to 3.65V, and the capacity retention rate after 500 cycles was calculated. The cycle capacity retention rates of the batteries 100 of the embodiments and comparative examples after 500 cycles at 25°C and a charge and discharge rate of 1C are shown in Table 2 below.
[0131] The capacity retention rate after 500 cycles at 25°C is calculated as follows: capacity retention rate after the 500th cycle = (discharge capacity after the 500th cycle / discharge capacity after the first cycle) × 100%.
[0132] Table 2 Performance parameters of the battery 100 of each embodiment and comparative example
[0133]
[0134]
[0135] It can be seen from the test results in Table 1 that when the first adhesive layer 122 and the second adhesive layer 123 are not set in Comparative Example 1, the negative electrode plate 130 of the battery 100 is severely wrinkled, but there is no material falling. In addition, the battery 100 of Comparative Example 1 has a lower 500-cycle cycle capacity retention rate. It can be seen from the test results of Examples 1 to 4 that, when the coating amounts of the first adhesive layer 122 and the second adhesive layer 123 are the same, as the content of the binder in the first adhesive layer 122 and the second adhesive layer 123 increases, the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110 and the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130 both gradually increase, and the cycle capacity retention rate of the battery 100 after 500 cycles gradually increases; in addition, (Fc·Wc) / (Fa·Wa) of Examples 1 to 4 are all between 0.85 and 6.36, and (Fc·Wa) / (Fa·Wc·P) are all between 0.05 and 1.39.
[0136] It can be seen from the test results of Examples 1 to 15 that no matter how the peel strength Fc between the first adhesive layer 122 and the positive electrode sheet 110, the coating amount Wc of the first adhesive layer 122 per unit area on the base film 121, the peel strength Fa between the second adhesive layer 123 and the negative electrode sheet 130, and the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121 are adjusted, as long as (Fc·Wc) / (Fa·Wa) is between 0.85 and 6.36, the negative electrode sheet 130 of the battery 100 will not have wrinkles, and the battery 100 has a high cycle capacity retention rate after 500 cycles. It can be seen from the test results of Comparative Examples 2 and 3 that when (Fc·Wc) / (Fa·Wa) is greater than 6.36, the negative electrode sheet 130 of the battery 100 will have severe wrinkles, and the cycle capacity protection rate of the battery 100 after 500 cycles is reduced. In Example 8, (Fc·Wc) / (Fa·Wa)=6.36, so the negative electrode plate 130 of the battery 100 has slight wrinkles, and thus the cycle capacity protection rate of the battery 100 after 500 cycles is relatively low.
[0137] It can also be seen from the test results of Examples 1 to 15 that when 0.85≤(Fc·Wc) / (Fa·Wa)≤6.3 and 0.05≤(Fc·Wa) / (Fa·Wc·P)≤1.39, the negative electrode plate 130 of the battery 100 will not only not be wrinkled, but also not easily drop. In Example 15, (Fc·Wa) / (Fa·Wc·P)=1.39, and in Example 8, (Fc·Wa) / (Fa·Wc·P)=2.12>1.39, so the battery 100 will drop slightly, so the cycle capacity protection rate of the battery 100 after 500 cycles is relatively low.
[0138] It can be seen from the test structures of Comparative Examples 4 to 7 that when the peel strength Fa between the second adhesive layer 123 and the negative electrode plate 130 and the coating amount Wa of the second adhesive layer 123 per unit area on the base film 121 are both 0 (i.e., there is only the first adhesive layer 122 and no second adhesive layer 123), by changing the coating amount Wc of the first adhesive layer 122 and the peel strength Fc between the first adhesive layer 122 and the positive electrode plate 110, the negative electrode plate 130 of the battery 100 will have wrinkles to varying degrees, and the cycle capacity protection rate of the battery 100 after 500 cycles is reduced.
[0139] See also Figure 7 The embodiment of the present application further provides an energy storage device 200 , which includes a box 210 and a plurality of batteries 100 described in the embodiment of the present application, wherein the plurality of batteries 100 are accommodated in the box 210 .
[0140] It can be understood that the multiple batteries 100 of the energy storage device 200 can be connected in parallel with each other; or in series with each other; or partially in parallel and partially in series (in other words, mixed connection). This application does not make any specific restrictions on the connection method of multiple batteries 100 of the same energy storage device 200.
[0141] Optionally, the energy storage device 200 may be at least one of a small energy storage box, a large energy storage cabinet, an energy storage module, etc. The present application does not specifically limit the form of the energy storage device 200. The form of the energy storage device 200 of the present application is merely one of its many forms and should not be understood as a limitation on the energy storage device 200 of the present application.
[0142] It should be noted that the stacking arrangement of the multiple batteries 100 can be that the multiple batteries 100 are arranged in sequence against each other, or the multiple batteries 100 are arranged in sequence and spaced apart. In addition, the multiple batteries 100 can be stacked in a transverse direction (such as a horizontal direction) or a longitudinal direction (such as a gravity direction). The stacking method and stacking direction of the multiple batteries 100 can be designed according to actual conditions.
[0143] It can be understood that the box body 210 has a receiving cavity (not shown), and multiple batteries 100 are received in the receiving cavity. In some embodiments, each receiving cavity receives one battery 100. In other embodiments, each receiving cavity receives multiple batteries 100.
[0144] See also Figure 8 and Fig. 9The embodiment of the present application also provides an energy storage system 300, which includes the energy storage device 200 and the electric energy conversion device 310 described in the embodiment of the present application, wherein the electric energy conversion device 310 is electrically connected to the energy storage device 200, the electric energy conversion device 310 is used to convert other forms of energy into electric energy, and the energy storage device 200 is used to store the electric energy.
[0145] Energy storage (i.e., energy storage) has a wide range of application scenarios, including power generation side energy storage, grid side energy storage, and power consumption side energy storage. The energy storage system 300 of the embodiment of the present application takes power generation side energy storage as an example to introduce the energy storage system 300 of the embodiment of the present application in detail, which should not be understood as a limitation on the energy storage system 300 of the embodiment of the present application, nor should it be understood as a limitation on the energy storage device 200 and the battery 100 of the embodiment of the present application.
[0146] Optionally, the electric energy conversion device 310 can convert at least one other form of energy such as solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0147] Optionally, the number of the electric energy conversion devices 310 may be one or more. When there are multiple electric energy conversion devices 310, the multiple electric energy conversion devices 310 may be connected in series, in parallel, or in mixed connection, which is not specifically limited in the present application.
[0148] Optionally, the electric energy conversion device 310 may be, but is not limited to, at least one of a photovoltaic panel, a wind power generation device, a hydropower generation device, and the like.
[0149] Optionally, the number of the energy storage devices 200 may be one or more. When the number of the energy storage devices 200 is multiple, the multiple energy storage devices 200 are connected in series or in parallel, which is not specifically limited in the present application.
[0150] When working, the power conversion device 310 is used to convert other forms of energy into electrical energy and store it in the energy storage device 200. The electrical energy stored in the energy storage device 200 can be supplied to electrical loads such as street lamps and household appliances for use when the electricity price is at a peak, or to supply power when the power grid is out of power. The electrical energy generated by the power conversion device 310 can also be supplied to the power grid through high-voltage cables to alleviate the power supply pressure of the power grid during peak hours.
[0151] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, if there is no contradiction between them.
[0152] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A battery, characterized in that: include: A positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, the separator comprises a base film, a first adhesive layer and a second adhesive layer, the first adhesive layer is located between the base film and the positive electrode sheet and is used to bond the base film to the positive electrode sheet, and the second adhesive layer is located between the base film and the negative electrode sheet and is used to bond the base film to the negative electrode sheet; The battery satisfies the relationship: 0.85≤(Fc·Wc) / (Fa·Wa)≤6.36; Among them, Fc is the peeling strength between the first adhesive layer and the positive electrode sheet, Wc is the coating amount of the first adhesive layer per unit area on the base film, Fa is the peeling strength between the second adhesive layer and the negative electrode sheet, and Wa is the coating amount of the second adhesive layer per unit area on the base film.
2. The battery according to claim 1, characterized in that The battery satisfies the relationship: 2.16≤(Fc·Wc) / (Fa·Wa)≤6.
20.
3. The battery according to claim 1 or 2, characterized in that: The range of the peel strength Fc between the first adhesive layer and the positive electrode sheet is: Fc≥2.1 N / m.
4. The battery according to claim 1 or 2, characterized in that: The range of the peel strength Fa between the second adhesive layer and the negative electrode sheet is: Fa≥0.5N / m.
5. The battery according to claim 4, characterized in that The peel strength Fa between the second adhesive layer and the negative electrode sheet is in the range of 0.5 N / m≤Fa≤2.2 N / m.
6. The battery according to claim 1 or 2, characterized in that: The coating amount Wc per unit area of the first adhesive layer on the base film is in the range of: 0.1 g / m 2 ≤Wc≤0.65g / m 2 The coating amount Wa of the second adhesive layer per unit area on the base film is in the range of: 0.1 g / m 2 ≤Wa≤0.65g / m 2 .
7. The battery according to claim 1, characterized in that The first adhesive layer and the second adhesive layer both include an adhesive, and the total mass proportion of the adhesive in the first adhesive layer and the second adhesive layer is P%. The battery also satisfies the relationship: 0.05≤(Fc·Wa) / (Fa·Wc·P)≤1.
39.
8. The battery according to claim 7, characterized in that The battery also satisfies the relationship: 0.05≤(Fc·Wa) / (Fa·Wc·P)≤0.
86.
9. The battery according to claim 7 or 8, characterized in that: The total mass percentage P% of the adhesive in the first adhesive layer and the second adhesive layer is in the range of: 2%≤P%≤25%.
10. An energy storage device, characterized in that: include: Box; as well as A plurality of batteries according to claim 9, wherein the plurality of batteries are housed in the casing.
11. An energy storage system, characterized in that: include: An electric energy conversion device and an energy storage device as described in claim 10, wherein the electric energy conversion device is electrically connected to the energy storage device, the electric energy conversion device is used to convert other forms of energy into electric energy, and the energy storage device is used to store the electric energy.
Citation Information
Cited By
Battery, energy storage device, and energy storage system
WO2026171018A1